HONOURABLE COURTSHIP IN THE CHURCH: TOWARDS A FRAMEWORK FOR VOCATIONAL DISCERNMENT - Olusesan Aina, Raymond (Asian Horizons, 2018)
Following the Church’s traditional teaching on the sacrament of marriage, Amoris Laetitia eulogises marriage as an esteemed vocation, which needs proper discernment and sustained preparation. The document devotes space to the discernment phases of betrothal and newly married. This contribution argues that Amoris Laetitia misses out on a necessary phase prior to betrothal. This is a specific period of discernment which has not been given its pastoral attention. This contribution offers a possible framework for pastorally assisting parties in courtship to discern adequately as they view marriage on the horizon. This vocational discernment consists of the features of what Gaudium et Spes calls honourable courtship, pastoral care for honourable courtship, and specific challenges to courtship in an African context.